Evolution of Janus Kinase 2 V617F-negative idiopathic myelofibrosis into Philadelphia+ chronic myeloid leukemia - Anu, Partanen; Esa, Jantunen (Journal of Clinical Case Reports and Images, 2023)
Limited data exist on the mechanisms promoting clonal expression of BCR-ABL1 cells in various myeloproliferative disorders. We present a patient whose Janus Kinase (JAK) 2 V617F-negative idiopathic myelofibrosis (IMF) transformed to Philadelphia-positive chronic myeloid leukemia (CML). A 55-year-old man had anemia and splenomegaly. Trephine biopsy showed excess fibrosis without a JAK2 V617F mutation. Diagnosis of high-risk IMF with t(3;12) and del(16q) was made. Five years later a repeated trephine biopsy showed extensive fibrosis and t(9;22) with der(22)t(9;22). BCR-ABL1 fusion gene with typical p210 fusion transcript was found resulting in the diagnosis of CML. A modest treatment response was achieved with tyrosine kinase inhibitor (TKI) therapies, but the disease eventually progressed to a myeloid blast phase. With AML-based chemotherapy plus azacytidine and a second generation TKI the patient survived for years but succumbed 11 years after the initial diagnosis. Clonal evolution may cause atypical disease characteristics or a poor response to targeted therapy in myeloproliferative disorders.
Keywords: myeloproliferative disorders; CML; BCR-ABL1 fusion gene; JAK V617F mutation